Ultrasonography as a diagnostic tool in orofacial swellings - Sunidhi Garg; Mysore K Sunil; Sahil Jindal; Ashwarya Trivedi; Eeraian N Guru; Sugandha Verma (Wolters Kluwer Medknow Publications, 2017)
Introduction: For several years, ultrasonography has played a major role as a diagnostic and therapeutic tool in various medical fields. Only recently has it been used for maxillofacial imaging. Aims and Objectives: To evaluate the reliability of ultrasonography as an alternative tool in the diagnosis of swellings in the orofacial region. Materials and Methods: Ultrasonographic examination of 30 patients of both the sexes aged between 8 and 70 years with swelling in the orofacial region was conducted. Doppler investigation was done in some cases to evaluate the vascularity. The following six sonographic parameters were recorded: shape, boundary echo, internal echo, distribution of internal echoes, posterior wall echoes, and vascularity. Following the clinical and ultrasonographic diagnosis, the lesion was subjected to histopathological examination and a final diagnosis was made. The ultrasonographic diagnosis was correlated with the clinical and histopathological diagnosis. Results: A significant association was observed between both clinical and histopathological diagnosis and ultrasonographic diagnosis (contingency = 0.888, P value = 0.000). Conclusion: Along with clinical and histopathological examinations, ultrasonography works out as a valuable adjunct in the diagnosis of orofacial swellings as it provides several advantages like it is non-invasive, easily reproducible, widely available, rapid, and inexpensive.